algebra

if (2 -q) is one factor of 4 - 2q - 6p + 3pq, what is the other factor?

a) 2 + 3p
b) 2 - 3p
c)3p - 2
d) 2 - 3q

  1. 👍 0
  2. 👎 0
  3. 👁 61
asked by ant
  1. You can use long division

    (4 - 2q - 6p + 3pq)/(2-q)

    2
    2*(2-q) = 4-2q
    subtract result is
    -6 p + 3 q
    divide by (2-q)
    -3p
    -3p(2-q) = -6p +3pq
    subtract, result is zero (remainder is 0
    so
    2-3p is the other factor

    1. 👍 0
    2. 👎 0
    posted by Damon

Respond to this Question

First Name

Your Response

Similar Questions

  1. algebra

    If (2 -q) is one factor of 4 - 2q - 6p + 3pq, what is the other factor? a)2 - 3p b)3p - 2 c)2 + 3p d)2 - 3q

    asked by ant on May 31, 2010
  2. Math please check

    p= -3; q=2 2q(p+q)+3pq I got -22

    asked by Katie on October 26, 2015
  3. MATH

    SIMPLIFY:p^2+pq-6q^2/p^2-3pq+2q^2

    asked by EMMA on January 5, 2017
  4. maths

    factorise p^2+q^2+2q-6q^2+3pq+4yz

    asked by tejaswi on August 19, 2013
  5. Pre calculus

    P=(-2,2) Q=(3,4) S=(2,-8) PS-3PQ Find the component form and magnitude of the vector.

    asked by Luis on April 3, 2014
  6. geometry

    diagonals of pqrs intersect each other at point a also ar = 3ap and as= 3aq, prove that sr =3pq

    asked by rishi on May 15, 2013
  7. Math

    In trapezium PQRS, the sides PQ and SR are parallel. Angle RSP is 120 . and RS = SP = 1/3PQ. What is the size of angle PQR ?

    asked by Amitabha on March 6, 2016
  8. science help

    Two factors which cause global climate change are listed below. Factor 1: Volcanic eruptions. Factor 2: Changes in the amount of Sun’s heat received by the Earth’s atmosphere and surface. Which of these statements is correct

    asked by Oscar on March 22, 2016
  9. itc c++

    can any one please dry run this code #include using namespace std; int main() { intnum,factor=1,temp; cout1) { factor = factor/10; cout

    asked by javeria on June 5, 2016
  10. MATH

    Factor by identifying a common factor in each term. g) 6xy2 = (3x) (?) h) 25a3b2 = (5a2b2) (?) i) 6x + 6y + 6p Factor: j) x(x+2) + y (x + 2) - 5(x + 2) k) 5y2 - 10y3 l) ax + ay + az Factor: m) yx(y+1) + 4x(y + 1) - 5(y + 1) n) 6p2

    asked by Anonymous on April 2, 2019

More Similar Questions